Oral versus intramuscular midazolam for paediatric preanaesthetic medication - Vyawahare, Kiran R.; Pahuja, Heena D.; Pande, Sushma T. (International Journal of Research in Medical Sciences, 2019)
Background: The need for effective preanesthetic medication in children is obvious and midazolam has proven to be one reliable choice. The aim of the present study was to compare the efficacy, acceptability and reliability of the oral and intramuscular routes of administration of midazolam towards paediatric preanesthetic medication at various doses. Methods: Hundred eligible patients in the age group of 1 to 10 years undergoing ambulatory or routine planned, minor or major surgery during study period were allocated to one of the four groups of 25 participants each, formed on the basis of premedication they received. Haemodynamic parameters, level of sedation and anxiety and induction score were noted before premedication and after each 15 minutes interval for next 45 minutes in all the four groups. Postoperative assessment included sleep level, anterograde amnesia, picture recall and occurrence of complications. Results: The sedative and anxiolytic effects were observed to be maximum at 45 minutes after premedication in all the four groups and better sedation, anxiolysis and quality of induction were achieved with higher doses for both oral as well as intramuscular routes. Postoperatively, the sleep level did not increase with higher dose and 64% patients were awake with 0.75 mg/kg oral midazolam. The sleep level was more with higher dose with the Intramuscular route, with 60% patients feeling drowsy with 0.1mg/kg dose. 0.75 mg/kg dose showed better anterograde amnesia (64%) than 0.5 mg/kg (28%), while it was present in 64% participants premedicated with 0.8 mg/kg intramuscular does and 72% in 0.1 mg/kg intramuscular dose. Conclusions: Intramuscular midazolam at 0.1 mg/kg dose seems to be the ideal dose and route for paediatric preanesthetic medication, with oral midazolam at 0.75 mg/kg to be considered an effective and acceptable alternative.